1995
DOI: 10.1007/bf02407230
|View full text |Cite
|
Sign up to set email alerts
|

Primary prevention as health and social competence promotion

Abstract: Primary prevention continues to be shackled by an implicit "magic bullet" perspective and an inoculationist mentality. The proliferation of short-term, uncoordinated programs co-exists with data showing that large segments of our teenage-and-younger population are exposed to conditions that are likely to harm their psychosocial growth. The status of primary prevention in the schools is shown pictorially as a jumbled confusion. An argument is made that coordination of interventions, centered around the goal of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0
3

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 27 publications
0
14
0
3
Order By: Relevance
“…In order to benefit students it is imperative, therefore, that strategies to improve emotional literacy and social and emotional competence are addressed in schools (Elias, 1995;Elias et al, 1997;Zins, Bloodworth, Weissberg and Walberg, 2004). Accordingly, in the United Kingdom some local education authorities (LEAs) are developing initiatives to improve emotional literacy (Weare and Gray, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In order to benefit students it is imperative, therefore, that strategies to improve emotional literacy and social and emotional competence are addressed in schools (Elias, 1995;Elias et al, 1997;Zins, Bloodworth, Weissberg and Walberg, 2004). Accordingly, in the United Kingdom some local education authorities (LEAs) are developing initiatives to improve emotional literacy (Weare and Gray, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Elsewhere (Cowen, 1994(Cowen, , 1996, I suggested that although such a view of primary prevention is legitimate in its own right, using it as the dominant definition of the concept is restrictive. Those articles stressed as others (Antonovsky, 1979;Elias, 1995) have, the need for the broader notion of wellness enhancement. DW's adoption of this two-factor definition of primary prevention led them, importantly, to assess both problem reducing and competence enhancing outcomes of such programs.…”
mentioning
confidence: 96%
“…Most continue to follow the tradition of providing adjunct services, marginal to the daily functioning of the school (Lee, 1993). The current, unenlightened system only provides students and families with the necessary attention and access to resources after a problem has escalated out of control (Elias, 1995;Romualdi & Sandoval, 1995). If counselors are going to be of help to educators and students, they need to increase access to both crisis intervention and case management services that are connected to the school life of the child (Knitzer et al, 1992).…”
mentioning
confidence: 99%
“…Because school service professionals often operate in isolation from each other, they frequently engage in a duplication of efforts or conflicting interventions (Adelman, 1993;Romualdi & Sandoval, 1995). Programs have failed to coordinate services within the school and community and the students have paid the price with inefficient and costly services, as well as a lack of continuity in programming for various problems and across grade levels (Elias, 1995;Adelman, 1993). In one New York school where there were 200 different prevention and treatment programs operating concurrently, even the principal could not identify the function of any of the programs (Dryfoos, 1993).…”
mentioning
confidence: 99%